2017
DOI: 10.1590/0100-29452017033
|View full text |Cite
|
Sign up to set email alerts
|

BIOLOGY OF POLLINATION OF Citrus sinensis VARIETY ‘PERA RIO’

Abstract: ABSTRACT-Aspects related to the floral biology of Citrus sinensis 'Pera Rio' variety were studied in the present work aiming to obtain information about the pollination ecology in the local agriculture. Studies of flowering, anthesis, pollen / ovule ratio, stigmatic receptivity, pollen viability, nectar characterization and floral visitors were carried out. From the data studied, the following information was obtained: C. sinensis variety 'Pera Rio' flourishes in two annual periods (dry and rainy), the anthesi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 17 publications
0
4
0
2
Order By: Relevance
“…A melissopalinologia pode contribuir para o rastreamento da origem geográfica de um determinado tipo de mel, uma vez que seu espectro polínico reflete a gama de recurso floral do local onde este mel específico foi produzido (EBENEZER; OLUGBENGA, 2010;SANTOS, 2011;SNIDERMAN, et al, 2018). Diferentes áreas geográficas apresentam associações florais particulares e quanto maior a diferença climática, mais notável é a variação na associação floral e ainda mais complexa é avaliação para determinação da sua origem botânica e geográfica (RICCIARDELLI; GALARINI; RICCIARDELLI, 2020;SNIDERMAN, et al, 2018).…”
Section: Introductionunclassified
“…A melissopalinologia pode contribuir para o rastreamento da origem geográfica de um determinado tipo de mel, uma vez que seu espectro polínico reflete a gama de recurso floral do local onde este mel específico foi produzido (EBENEZER; OLUGBENGA, 2010;SANTOS, 2011;SNIDERMAN, et al, 2018). Diferentes áreas geográficas apresentam associações florais particulares e quanto maior a diferença climática, mais notável é a variação na associação floral e ainda mais complexa é avaliação para determinação da sua origem botânica e geográfica (RICCIARDELLI; GALARINI; RICCIARDELLI, 2020;SNIDERMAN, et al, 2018).…”
Section: Introductionunclassified
“…Therefore, it could be considered as a gentle factor which provides a lower yield. The pollen-ovule ratio was slightly lower (1176.45 : 1) in comparison to Citrus sinensis (Ribeiro et al 2016). Pollen-ovule ratio is an indicator of the reproductive system of plants (Cruden 1977).…”
Section: Discussionmentioning
confidence: 87%
“…Two types of flowers (her maphrodite and staminate) were also observed in Citrus sinensis (Kumatkar et al 2016). However, Ribeiro et al (2016) reported the presence of infertile ovary with ter minal inclusion of stylet and undivided stigma. The ratio of hermaphrodite to male flowers was higher during early to mid flowering phase and lesser during the later half of the flo wering stage.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations